Rheological and Tribological Properties of Functionalized Polymer Nanocomposites - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier, 2024)
Polymer nanocomposites (PNCs) have grown into a fashionable area of recent research with high concert, conquering the flaws of mass polymers (Ps) and meeting the demands of civilization and the market in tribological and rheological applications. Ps together with ultrahigh molecular mass Ps are hugely widespread Ps in present-day research in rheology, including tribology. This study accurately analyses current PNC advancements in tribology and rheology. The effects of various nanofiller (NF) divisions, such as carbon-based, silicon-based, and hybrid fillers combined with metal oxide, on the rheological and tribological applications of PNCs are investigated. Because the rheological and tribological actions of PNCs are never innate, nevertheless, they rely on sliding assets and direct co-relation surrounded by distinct divisions of NF as a choice of similar NF of differing morphologies and structures is never reasonable. Wear and irritation rates are fair to indicate provisional enhancement through different NFs. Prominence is simulated to the effect of NF absorption and superficial functionalization of NFs for wear resistance, irritation, transfer film arrangement, and wear structure like its composites. Constraints and forthcoming research capacity on rheology, together with tribology of PNCs, are concluded. © 2024 Elsevier Ltd. All rights reserved.